2022
DOI: 10.3390/f14010032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Ability of SLSTR (Sentinel-3B) and MODIS (Terra) Images to Detect Burned Areas Using Spatial-Temporal Attributes and SVM Classification

Abstract: Forest fires are considered one of the major dangers and environmental issues across the world. In the Cerrado biome (Brazilian savannas), forest fires have several consequences, including increased temperature, decreased rainfall, genetic depletion of natural species, and increased risk of respiratory diseases. This study presents a methodology that uses data from the Sea and Land Surface Temperature Radiometer (SLSTR) sensor of the Sentinel-3B satellite and the Moderate Resolution Imaging Spectroradiometer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…In Figur can be seen that in Brazil, the reference burned area reached 8.88 km 2 , while in Portu exceeded the value of 93 km 2 (Figure 2). In the state of Piauí in Brazil, in the Cerrado biome, the authors [9] used data from the Sea and Land Surface Temperature Radiometer (SLSTR) sensor of the Sentinel-3B satellite and the Moderate Resolution Imaging Spectroradiometer (MODIS) of the Terra satellite to analyze the thematic accuracy of burned area maps and their sensitivity under different spectral resolutions. The authors used the methodology of training and the Support Vector Machine (SVM) classifier and found that the main problems associated with spectral mixing, registration date, and spatial resolution of 500 m were the main factors that led to commission errors ranging between 15% and 72% and omission errors between 51% and 86% for both sensors.…”
mentioning
confidence: 99%
“…In Figur can be seen that in Brazil, the reference burned area reached 8.88 km 2 , while in Portu exceeded the value of 93 km 2 (Figure 2). In the state of Piauí in Brazil, in the Cerrado biome, the authors [9] used data from the Sea and Land Surface Temperature Radiometer (SLSTR) sensor of the Sentinel-3B satellite and the Moderate Resolution Imaging Spectroradiometer (MODIS) of the Terra satellite to analyze the thematic accuracy of burned area maps and their sensitivity under different spectral resolutions. The authors used the methodology of training and the Support Vector Machine (SVM) classifier and found that the main problems associated with spectral mixing, registration date, and spatial resolution of 500 m were the main factors that led to commission errors ranging between 15% and 72% and omission errors between 51% and 86% for both sensors.…”
mentioning
confidence: 99%